Rancang Bangun Pendinginan Suhu Pada Jaket Menggunakan Mikrokontroler Berbasis Android - yaumil irana; Waluyo Waluyo; M. Nanak Zakaria (Politeknik Negeri Malang, 2021)
Physical exercise is an activity carried out to maintain a healthy body condition. Health is the most important part of all activities carried out by humans by paying attention to vital signs such as body temperature, heart rate, and others on a regular basis. Regular physical exercise for a long time, which is about 30 minutes, can cause changes in bodily functions. The acute effect of excessive physical exercise results in an increase in heart rate and body temperature. This study is designed to control and monitor body temperature as well as other vital signs of health during exercise, and to avoid excessive physical exercise. Research that has been conducted previously obtained the results of values before exercise for body temperature using infrared and ds18b20 which have a range between 34.550C - 36.090C and 35.060C - 36.190C, values for skin moisture range from 47% and heart rates between 94 Bpm - 118 Bpm. Meanwhile, during the exercise, the body temperature is between 36.380C - 36.810C, skin moisture between 47% - 15%, and a heart rate between 105 Bpm - 95 Bpm with a value of delay between 0.034897000s - 0.037563000 s during the live streaming. Based on this research, it can be concluded that the fan can turn on automatically and successfully reduce the user's body temperature gradually with a temperature range between 35,000C - 36.80C.